Tipologi Guru dan Otoritasnya dalam Transmisi Ilmu Pengetahuan - Diana Munawwarah, Ummu; Asiawati, Linda; Rokib, Moh.; Septi Anggraini, Diana (Kartika: Jurnal Studi Keislaman, 2025)
Islamic education presents a comprehensive and integral concept encompassing cognitive, spiritual, moral, and social dimensions. In the perspective of classical Muslim scholars such as Ibn Sina and al-Ghazali, the teacher plays a fundamental role not only as a transmitter of knowledge but also as a guide, moral educator, and character builder. This study aims to analyze the typology of teachers and their authority in the transmission of knowledge within the framework of classical Islamic educational thought. The research employs a qualitative approach with a descriptive design, using a literature study based on classical and contemporary scholarly works related to Islamic education. The findings reveal that in the Islamic educational tradition, teachers hold diverse typologies mu’allim, mu’addib, mudarris, shaykh, and ustadz each embodying distinct responsibilities and functions. A teacher’s authority is derived not only from intellectual mastery but also from moral integrity and spiritual exemplarity. Consequently, the teacher occupies a central position in shaping the balance between knowledge and ethics, serving as a key figure in maintaining the continuity of knowledge transmission within the Muslim intellectual tradition.